Intravenous Sildenafil in the Management of Pulmonary Hypertension Associated with Congenital Diaphragmatic Hernia - Bialkowski, Anja; Moenkemeyer, Florian; Patel, Neil (European Journal of Pediatric Surgery, 2015)
Background Pulmonary artery hypertension (PAH) is a significant cause of morbidity and mortality in infants with congenital diaphragmatic hernia (CDH). The phosphodiesterase-5 inhibitor sildenafil may be beneficial as a pulmonary vasodilator in CDH. Use of oral preparations of sildenafil may be restricted by feeding delays and intolerance. This study assessed the cardiorespiratory effects of a newly available intravenous (IV) preparation of sildenafil in CDH.Objectives The objective of the article is to assess the acute effects of IV sildenafil infusion on myocardial function, pulmonary artery pressure (PAP), and oxygenation in infants with CDH.Methods Retrospective case review of infants with CDH who received continuous IV sildenafil. Physiological and echocardiographic data were reviewed to obtain oxygenation index (OI), PAP, patent ductus arteriosus (PDA) flow, myocardial tissue Doppler velocities, and right ventricular output (RVO) at 48 hours presildenafil, and at 24 to 48 hours and 72 to 96 hours after commencing IV sildenafil.Results A total of nine infants received IV sildenafil at a dose of 100 to 290 μg/kg/h after CDH repair but before enteral feeding. Pre-IV sildenafil PAP was ≥ systemic blood pressure in all infants, systolic and diastolic right ventricular myocardial velocities were impaired. After 72 to 96 hours of IV sildenafil, OI and Fio2 were significantly reduced. Ratio of right-to-left to left-to-right PDA flow was > 1 pre-IV sildenafil and < 1 post-IV sildenafil.Conclusions IV sildenafil infusion was associated with improved oxygenation. Prospective trials of IV sildenafil are required to determine effects on longer term outcome.
Keywords: congenital diaphragmatic hernia; pulmonary hypertension; intravenous sildenafil; phosphodiesterase 5 inhibitor; newborn infant